1996
DOI: 10.1590/s0034-89101996000200003
|View full text |Cite
|
Sign up to set email alerts
|

Determinação das fontes alimentares de Anopheles aquasalis (Diptera: Culicidae) no Estado do Rio de Janeiro, Brasil, pelo teste de precipitina

Abstract: ResumoAnopheles aquasalis é um mosquito ora encarado como antropofílico, ora como zoofílico ou eclético. Realizou-se estudo em Guapimirim, Estado do Rio de Janeiro, de maio a novembro de 1992, com o intuito de se verificar a fonte alimentar preferida desse anofelino através de teste imunológico de precipitina. De 1.366 fêmeas capturadas em abrigos naturais, 725 estavam ingurgitadas. O conteúdo digestivo de apenas 473 delas reagiu no teste de precipitina, sendo que em 75,3% dos casos foi identificada apenas uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…aquasalis caught in the municipality of São José de Ribamar. Similar to the findings of Flores-Mendonza et al [35], who identified a variety of blood meal sources used by this species of anopheline. Both of these authors used the precipitin test.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…aquasalis caught in the municipality of São José de Ribamar. Similar to the findings of Flores-Mendonza et al [35], who identified a variety of blood meal sources used by this species of anopheline. Both of these authors used the precipitin test.…”
Section: Discussionsupporting
confidence: 88%
“…feeding on human blood [6]. Therefore, some researchers have suggested that the classification of the feeding habits of this species should be changed from zoophilic to eclectic or opportunistic [5, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Adults, once again, are opportunistic, feeding indoors or outdoors on animal or human hosts, but generally resting outdoors before and after feeding [100,110-112]. Biting tends to begin at dusk, peaking early in the night, and tailing off as the night progresses [111,112] (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…aquasalis é considerado um anofelino dotado de variável comportamento alimentar quanto à fonte sangüínea (Senior-White 16 , 1952) sendo capaz de sugar, espontaneamente, homem, boi, cavalo, porco, cão e aves, mostrando preferência por animais de grande porte (Flores-Mendoza et al 6 , 1996). Normalmente, é considerado um vetor muito menos importante que An.…”
Section: Flutuação Sazonalunclassified